Imbedding Gender Issues in English Materials for University Students - Puspita Dewi; Abdul Muhid; Hilda Hastuti (Humanitatis : Journal of Language and Literature, 2023)
Gender inequality becomes one of the most challenging issues all over the world because it is one of Sustainable Development Goals (SDGs) targets and Education for All (EFA) goals to reduce gender inequality in society. Education has a pivotal role in reducing and solving social problems because education through the teaching and learning process and the materials available could shape students’ minds and perspectives. Consequently, selecting good values and vibes in the materials are needed. Most textbooks are concerned with skills and cutting-edge technology issues. One of the illustrations is English textbooks for computer science that focus on how to be a good programmer and game developer but the materials neglect the social values, contexts, and function. The aim of this study is to develop English materials gender-based content for Computer science students as well as to promote gender equality to students. The method of this study is Research and Development (R&D) proposed by Gall, Gall, & Borg. The instruments are classified into two aspects namely questionnaire and interview. It is expected that the materials developed could reduce gender inequality in the academic environment because, through textbooks or materials, teachers are able to change the students’ perspectives and behaviors. The research results show that the students believe that the materials based on gender content can encourage them to learn English and they are enthusiastic to learn the subject.